Mindfulness as a Buffer of Leaders’ Self-Rated Behavioral Responses to Emotional Exhaustion: A Dual Process Model of Self-Regulation - Megan M. Walsh (Frontiers in Psychology, 2018)
In this study, we investigate the self-regulatory role of mindfulness in buffering the relationship between leaders’ emotional exhaustion and self-rated leadership behavior (transformational leadership and abusive supervision). Specifically, we propose that leader mindfulness buffers the relationship between emotional exhaustion and both negative affect and impaired perspective taking, which link leader emotional exhaustion and leadership behavior (i.e., moderated mediation). Using a time-lagged survey of leaders (N = 505) we found that leader perspective taking and negative affect mediated the relationships between emotional exhaustion and self-reported leadership behavior. Furthermore, we found that leader mindfulness buffers the relationship between emotional exhaustion and negative affect, which weakened the mediated relationship between emotional exhaustion and both transformational leadership and abusive supervision. However, leader mindfulness did not moderate the relationship between emotional exhaustion and perspective taking. Theoretical and practical implications are discussed.